2021
DOI: 10.1016/j.ijid.2020.10.099
|View full text |Cite
|
Sign up to set email alerts
|

Viral kinetics of SARS-CoV-2 over the preclinical, clinical, and postclinical period

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 3 publications
4
39
1
Order By: Relevance
“…Thus, RATs for NP swabs can be promising tools for the rapid detection of SARS-CoV-2 for patients in the initial phase of symptomatic infection and/or with high viral loads. However, sensitivity for specimens with lower viral loads and for specimens collected after 7-days PSO gradually decreased, and antigen kinetics showed a more acute decrease in COI for both RATs with an increase in Ct values, which was consistent with the results of previous studies [ 11 , 14 , 15 ]. Moreover, several studies reported that NP specimens with Ct > 25 do permit recovery of virus from viral culture, and this is possible even for Ct > 35 [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, RATs for NP swabs can be promising tools for the rapid detection of SARS-CoV-2 for patients in the initial phase of symptomatic infection and/or with high viral loads. However, sensitivity for specimens with lower viral loads and for specimens collected after 7-days PSO gradually decreased, and antigen kinetics showed a more acute decrease in COI for both RATs with an increase in Ct values, which was consistent with the results of previous studies [ 11 , 14 , 15 ]. Moreover, several studies reported that NP specimens with Ct > 25 do permit recovery of virus from viral culture, and this is possible even for Ct > 35 [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…As highlighted by other authors [ 34 , 36 ], timing since disease onset must be acknowledged as well. Data of temporal profiles of SARS-CoV-2 show that the number of RNA copies peaks close to symptom onset and tapers steeply by the end of the first week [ 9 , 21 , 22 ]. Thus, finding different Ct values in infected patients may tell more about the disease’s timing than the severity itself [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A key aspect in response to the COVID-19 pandemic has been the early detection and prompt isolation of infected patients [ 4 ]. For this purpose, real-time reverse transcriptase-polymerase chain reaction (RT-PCR) has been regarded as the gold standard diagnostic test [ 5 ], with an estimated 70 and 95 % sensitivity and specificity, respectively [ 6 ] RT-PCR reveals the broadest range of detection: becoming positive days before symptom onset and detecting viral nucleic acids up to several weeks in infected patients [ 7 9 ]. However, it is essential to clarify that test performance may differ due to the inherent variability between assays, extraction method/instrument combination, targeted regions of the viral genome, and clinical matrix tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the lower the Ct value obtained, the more the gene exists in the sample, which can represent a higher viral load [ 216 ]. Despite the recommendation to perform the RT-qPCR test on samples collected from the appearance of symptoms, since the viral load is higher [ 217 ], some studies indicate that the Ct value between symptomatic and asymptomatic patients is similar [ 218 , 219 , 220 ]. This indicates that even if the appearance of symptoms is important for the performance of molecular tests, since it is related to the increase in viral load, these tests can also be used in samples from asymptomatic patients, once the found Ct value can be similar.…”
Section: Nucleic Acid-based Tests and Serological Tests: Practicalmentioning
confidence: 99%